Global Equity Country Allocation: An Application of Factor Investing. Issue 4 (1st October 2017) - Angelidis, Timotheos; Tessaromatis, Nikolaos
Abstract : Under the paradigm of factor investing, we create a global factor allocation strategy using country indexes and portfolio construction methodologies that are robust to estimation error. Implementable through exchange-traded funds or index futures, a portfolio based on country indexes with favorable factor exposures significantly outperforms, both economically and statistically, the world market capitalization portfolio. The outperformance remains significant after taking into account transaction costs, alternative portfolio construction methodologies, and tracking error constraints. From a practical investment perspective, country-based factor portfolios offer a viable alternative implementation of factor investing in a world of illiquidity, transaction costs, and capacity constraints. Abstract : Disclosure: The authors report no conflicts of interest. Editor's Note This article was externally reviewed using our double-blind peer-review process. When the article was accepted for publication, the authors thanked the reviewers in their acknowledgments. Ronnie Shah, CFA, was one of the reviewers for this article. Submitted 20 August 2016 Accepted 26 May 2017 by Stephen J. Brown